(untitled) (Research, Society and Development, 2021)
This study evaluated the mobility and persistence of aldicarb and its degradation products in red-yellow oxisol (LVA) using soil columns, after the application of Temik 150. Leaching experiments were performed using polyvinyl chloride (PVC) columns filled with soil contaminated with aldicarb and rain simulation of 6.05 mm day-1, at 10 day intervals, for 90 days. Aldicarb, aldicarb sulfoxide and aldicarb sulfone residues were extracted from soil (solid-liquid) and percolated water (liquid-liquid) samples with quantification by CG-FID. The results showed that aldicarb was rapidly oxidized to aldicarb sulfoxide and aldicarb sulfone in 10 days after the application. Aldicarb sulfoxide percolated through 15 cm of the soil column and could not be detected in the soil after 40 days incubation. From the 60 days since application, residues were no longer detected in the samples of percolated water and soil fractions, indicating rapid degradation and low potential for groundwater contamination.